Challenging role of myokines in heart failure - Berezin, A. E.; Berezin, A. A.; Березін, Олександр Євгенійович (London: iMedPub LTD, 2020)
The aim of the narrative mini review is depicted the role of the myokines in patients with heart failure (HF). The myokines (irisin, myostatin, myonectin, brainderived neurotrophic factor, interleukins [IL]-6, IL-8, IL-15, tumor necrosis factoralpha, fibroblast growth factor 21, growth differential factor-11) are produced predominantly by skeletal muscle cells in response to physical activity and regulate metabolic homeostasis, proliferation, angiogenesis, neovascularization, reparation and neurogenesis in skeletal muscle tissue. HF is strongly associated with decrease in physical endurance and led to myopathy having established negative impact on the clinical outcomes and quality of life. Impaired myokine profile has been found in patients with HF regardless of phenotypes of cardiac dysfunction and, so important, prior to sarcopenia. It has been postulated that altered profile of the myokines can improve a stratification of HF patients at higher risk of poor clinical outcomes independently left ventricular ejection fraction and metabolic disease presentation.
Keywords: Heart failure; Myokines; Outcomes; Sarcopenia; Risk stratification; Prognosis